Zhodnocení efektivity investic do vzdělávání zaměstnanců veřejného sektoru - Kerlesová, Vladislava (Univerzita Pardubice, 2010)
Education is a continual process of acquiring knowledge, accomplishments and skills, which contribute not only to cultivation of the individual, but also of the entire society. The public enterprise is a domain which supports the education of employees, as its goal is the contentment of the broad public. The article presents the results of an analysis which shows the positive approach of the public enterprise to education, furthermore it shows the employee’s interest in education.
Keywords: questionnaire; public sector; education process; personnel